Combined Straw and Plastic Film Mulching Can Increase the Yield and Quality of Open Field Loose-Curd Cauliflower - Xie, Yandong; Li, Jinwu; Jin, Li; Wei, Shouhui; Wang, Shuya; Jin, Ning; Wang, Junwen; Xie, Jianming; Feng, Zhi; Zhang, Guobin; Lyu, Jian; Yu, Jihua (Frontiers in Nutrition, 2022)
To evaluate the impact of straw mulching on the production of open field loose-curd cauliflower, this study analyzed the 'Feicui No. 9' cauliflower variety, grown in field trials in Northwest China, in 2019 and 2020. Plots in an open field were prepared without mulch (CK1) and with plastic film mulch (CK2), as experimental controls, along with three experimental mulching methods, including dual straw and plastic film mulch (T1), inter-row straw mulch (T2), and full straw mulch (T3). The effects of the different ground cover alternatives on loose-curd cauliflower’s dry matter accumulation, yield, quality, and volatile compounds, were explored. The results showed that, compared with CK2 treatment, T1 treatment promoted the accumulation of dry matter, and increased the economic and biological yield, by 12.98% and 6.51%, respectively. The soluble sugar and vitamin C content in loose-curd cauliflower heads, subjected to T1 treatment, increased by 18.46% and 8.12%, respectively, and the nitrate content decreased by 25.57%. Moreover, the T1, T2, and T3 treatments significantly increased the levels of macro-, meso-, and microelements. Headspace solid-phase microextraction-gas chromatography-mass spectrometry (HS-SPME-GC-MS) was used to determine the volatile substances in loose-curd cauliflower heads from the 2020 harvesting period. Detected compounds included 17 aldehydes, 15 ketones, 10 alcohols, 15 esters, 29 hydrocarbons, 12 nitrogen-containing compounds, and 17 other substances. T1, T2, and T3 treatments increased the volatile substance content, whereas T1 treatment increased the quantity of volatile substances. In summary, dual mulching with straw and plastic film could promote dry matter accumulation, significantly increase the yield and quality, and effectively improve the flavor of loose-curd cauliflower. This mulching technique can be applied to open field vegetable and corn production areas, providing technical and theoretical support for the realization of high-yield, high-quality production models and a new straw recycling method.